The Perifiton Alga Community in Masang Kecil River Receives Liquid Palm Oil Mill Waste in Kinali District, West Pasaman Regency - Vivi Safitri; Izmiarti Izmiarti; Jabang Nurdin (Jurnal Biologi Universitas Andalas, 2019)
The study of the periphyton algae community in Masang Kecil River that received palm oil mill effluent in Kinali District, West Pasaman Regency was held from November 2017 to September 2018. This study aims to determine the composition and structure of periphyton communities in the Masang Kecil River in Kinali, West Pasaman. This study used purposive sampling method with a sampling location of 4 stations. Based on this study, 88 species of periphyton were classified as 3 classes i.e Bacillariophyceae (64 species), Chlorophyceae (15 species) and Cyanophyceae (9 species). The average density is 8.967 ind/ cm2.  The highest relative density (KR) at stations 1,2 and 3 is Navicula lanceolata and station 4 is Fragilaria capucina. Species that are always found at each station (FK= 100%) are Fragilaria capucina, Navicula lanceolata and Synedra ulna. The diversity index in the Masang Kecil River is classified as medium (H’ = 2.87). Equitability index is evenly distributed (E= 0.64). Dominance index (C= 0.12) there is no dominant  species. The similarity index is almost the same except between stations 1 and 3.